PRINSIP DIFERENSIASI AL QUR’AN PERSPEKTIF MUHAMMAD SHAḤRŪR - Ahmad Fajar Rofiq (QOF, 2020)
This research is a study of deconstruction carried out by Shahrur about key terms in the Qur'an. Among them are al-Kita>b, al-Qur’a>n, al-Dhikr, Tafs}i>l al-Kita>b and al-Furqa>n which terms are often simply equated. Whereas for Shah{ru>r these terms have substantial differences, both in terms of their characteristics and content. The problem finally led Shah{ru>r to do a reconstruction of these themes. Shaḥrūr argues that synonymy is merely a hoax in the sense that it can reduce concepts to each of the key terms in the Qur'an. Every word in the Qur'an will lose its content and depth. Therefore, by rejecting synonymy, Shaḥrūr has explored the key terms above which turned out to be different from what is understood by the mainstream Muslim community so far. The author finds that one of the differentiations made by Shah{ru>r is related to the distinction between al-Kitāb and al-Qur'ān, Shaḥrūr refers to verse tilka a>ya>t al-kita>b wa qur’a>nin mubi>nin. (Q.S al-Hijr : 1) The word qur'a> n which is interpreted in the word al-kita>b indicates that between al-kitab and al-qur'a>n are different. From the results of the study that has been done, the principle of Shaḥrūr differentiation has brought implications and significance to the building of the science of the Qur'an. Among them are the concepts of i'jāz, asbāb al-nuzūl, muhkam-mutashābih, and interpretive methodologies in understanding each theme in the Qur'an, because of different content of Qur’an